UTILIZATION OF BAITED DRIFT FADS ON HANDLINE IN PALABUHANRATU BAY WATERS - Mawardi, Wazir; Wahju, Ronny Irawan; Mustaruddin, Mustaruddin; Sabirah, Haifa; Zulkarnain (Departemen PSP IPB, 2025)
Handline fishermen in Palabuhanratu are small-scale fishermen who have limited access to science and technology. This condition has an impact on low catch productivity. Therefore, to overcome this problem, an effective fish collection technology is needed, namely the baited drift fish aggregating device (FAD). This study aims to construct a baited drift fish aggregating device operated by a handline fishing boat as a treatment handline, compare the composition of the catch, determine the effect of using baited drift fish aggregating devices, determine productivity and determine the production margin of the treatment handline catch compared to the control. The experimental fishing method was carried out with 16 trips as replications provided a higher catch result for the treatment handline compared to the control with a total catch of 98.67 kg and 62.34 kg, respectively. Based on the results of the Mann-Whitney analysis, the treatment handline had a significant effect on the number of fish and the weight of the catch. The productivity of the treatment handline had a greater value than the control handline, namely 6.17 kg/trip and 3.90 kg/trip respectively with the production margin of the treatment handline catch compared to the control for weight units and individual increasing by 58.28% and 76.2% respectively. Key words: attractor, baited, FADs, handline, Palabuhanratu Bay